EPIDEMIOLOGICAL ASPECTS OF HIV-TB CO-INFECTION IN PEOPLE WITH HIV/AIDS (PLWHA): A HOSPITAL-BASED STUDY - Sitorus, Rico januar; Murinata, Jaka; Antara, Nyoman Yudi; Sangalang, Reymart V.; Panjaitan, Merry Natalia (Universitas Airlangga, 2024)
Introduction : Tuberculosis (TB) is one of the co-infections with high morbidity and mortality in patients with HIV/AIDS (PLWHA). The prevalence of Tuberculosis in HIV patients in Indonesia ranges from 19.7% to 61.5%. Aims: This study aimed to identify predictors of incident HIV-TB co-infection in PLWHA. Methods: This observational study used a case-control design. Cases were defined as patients with HIV/AIDS co-infected with TB, while controls were those with HIV/AIDS without TB co-infection. The study population included 180 PLWHA, comprising 60 cases and 120 controls. Exclusion criteria for the case group were patients who had not completed their medical records and those who were previously infected with TB before HIV infection. Results: Bivariate analysis showed that variables significantly related to TB-HIV were clinical stage, CD4 levels, anemia status, and opportunistic infections. Multivariate logistic regression analysis showed that CD4 levels were the dominant predictor, with an adjusted odds ratio (AOR) of 5.71, 95% confidence interval (CI) 2.84-11.84, p = 0.0001. Meanwhile, clinical stage, anemia status, and opportunistic infections were confounding variables. Conclusion: CD4 levels were found to be a dominant predictor of increased TB-HIV risk. Further efforts should be made to encourage home assistant care initiation and improve medication compliance based on these results.